Topical Diclofenac Therapy for Mondor’s Disease of the Breast - Mosah, Hamoudi; Mahmood, Estabraq; Jabber, Maher (AL-Kindy College Medical Journal, 2012)
Background: Mondor’s disease means superficial thrombophlibitis of the chest wall in human, treatment is entirely symptomatic. Hot, wet dressing and anodynes may be used for pain relief. Objective: To evaluate the role of systemic and transdermal action of diclofenac (olfen) with respect to the symptom and sign (pain, erythema along the superficial vein), and the use of Doppler ultrasonography which is a colored ultrasound used for assessment of flow of blood in vessels. Method: The study was performed on 12 cases with Mondor’s disease in middle age female patients with the involvement of lnframammary veins in all of the them (commonly affected), 4 cases had reassurance only, 4 cases had reassurance with systemic diclofenac, and the other 4 cases had reassurance with topical olfen patch. Results: Olfen patch exerts a strong and rapid action in topical olfen cases, regarding it is role in subsiding the inflammatory process of the veins and so relieving pain with fastening the healing rate as minimum as possible (1 week), thereby abolishing the role of surgery in resistant cases. Conclusion: Olfen patches play a major role in treating cases with mondor’s disease by reducing inflammatory process through its transdermal migration action of diclofenac and within a short time by achieving a high local concentration.